Evaluation of skin prick location on the forearm using a novel skin prick automated test device - Seys, Sven F.; Gorris, Senne; Uyttebroek, Saartje; Backaert, Wout; Jorissen, Mark; Schrijvers, Rik; Daems, Rembert; Loeckx, Dirk; Van Gerven, Laura; Hellings, Peter W. (Frontiers in Allergy, 2023)
Background The skin prick test (SPT) is the gold standard for identifying allergic sensitization in individuals suspected of having an inhalant allergy. Recently, it was demonstrated that SPT using a novel skin prick automated test (SPAT) device showed increased reproducibility and tolerability compared to the conventional SPT, among other benefits. Objective This study aimed to evaluate prick location bias using the novel SPAT device. Methods A total of 118 volunteers were enrolled in this study and underwent SPATs with histamine (nine pricks) and glycerol control (one prick) solutions on the volar side of their forearms. Imaging of the skin reactions was performed using the SPAT device, and the physician determined the longest wheal diameter by visually inspecting the images using a web interface. Prick location bias was assessed along the medial vs. lateral and proximal vs. distal axes of the forearm. Results In total, 944 histamine pricks were analyzed. Four medial and four lateral histamine pricks were grouped, and wheal sizes were compared. The longest wheal diameters were not significantly different between the medial and lateral prick locations (p = 0.41). Furthermore, the pricks were grouped by two based on their position on the proximal–distal axis of the forearm. No significant difference was observed among the four groups of analyzed prick locations (p = 0.73). Conclusion The prick location on the volar side of the forearm did not influence wheal size in SPAT-pricked individuals.